(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The maximum principle is a fundamental concept in mathematics and engineering, providing crucial insights into the behavior of various mathematical and physical systems. This principle has wide-ranging applications in fields such as differential equations, optimal control, and numerical analysis. Error analysis, on the other hand, plays a critical role in assessing the accuracy and reliability of numerical methods and computational algorithms. This article discusses the maximum principle and its significance in error analysis, highlighting its applications and implications in various disciplines.